Peacebuilding Pesantren: The Study of Madurese Diaspora in Reinforcing Social Resilience in Post-ethnic Conflicts West Kalimantan, Indonesia - Rozaki, Abdur; Izudin, Ahmad (Ulumuna, 2025)
Research on the involvement of the Madurese diaspora in West Kalimantan in establishing pesantren (Islamic boarding schools) and their contributions to peace resilience remains limited. This study aims to investigate why and how the Madurese diaspora engages in peace resilience through the establishment of pesantren. Data were gathered through observations, semi-structured interviews, and document analyses using a multiple-case study approach. The results suggest that pesantren have played a vital role in promoting harmony and peace among different ethnic groups through re-education, community empowerment, and interfaith dialogues. This has significant implications for social harmony, cooperation (Handep), social cohesion, solidarity, and the mitigation of ethnic-based provocations. The involvement of pesantren presents a novel perspective on reconstructing strategies for addressing interethnic conflicts, thereby introducing a new cultural construction approach as a framework for future conflict resolution mechanisms.